Finite Element Analysis Could Predict and Prevent a Pathological Femoral Shaft Fracture after En Bloc Resection of a Large Osteoid Osteoma - Tadashi Iwai; Naoto Oebisu; Manabu Hoshi; Naoki Takada; Hiroaki Nakamura (MDPI AG, 2022)
Osteoid osteoma is a benign tumor. Approximately 20% of these tumors are located in the femur. The tumor primarily occurs in children and is treated by surgical excision or radiofrequency ablation. Recently, bone-tumor resection using three-dimensional (3D) intraoperative imaging with an O-arm in combination with a navigation system has been reported to be effective. However, there is a risk of postoperative fracture because of the weakening of the bone after drilling for tumor resection. A 12-year-old Japanese girl presented with an osteoid osteoma in the left femoral shaft, which resulted in a fracture after en bloc resection and artificial bone grafting using a 3D image-guided (O-arm) assisted navigation system. Orthopedic oncologists should be aware of the risk of fracture. Moreover, they should consider the mechanical risk prediction of bone fracture using finite element analysis prior to treatment.